Di văn thời Tây Sơn trên đất Thăng Long - Hà Nội - Trần, Nghĩa; Lâm, Nghĩa; Vũ, Thanh Hằng; Phạm, Văn Thắm; Nguyễn, Doãn Tuân (Nxb. Hà Nội, 2010)
Gồm: Văn kiện triều đình; tác phẩm văn nhân; di văn nơi phường, xã.